2011
DOI: 10.1007/s00028-011-0129-8
|View full text |Cite
|
Sign up to set email alerts
|

Discrete fragmentation with mass loss

Abstract: We examine an infinite system of ordinary differential equations that models a discrete fragmentation process in which mass loss can occur. The problem is treated as an abstract Cauchy problem, posed in an appropriate Banach space. Perturbation techniques from the theory of semigroups of operators are used to establish the existence and uniqueness of physically meaningful solutions under minimal restrictions on the fragmentation rates. In one particular case an explicit formula for the associated semigroup is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…Another approach, that is the subject of this paper, is based on semigroup theory, see e.g. [8], and consists in looking at (1) (or (6)) as a perturbation of the linear fragmentation semigroup by the nonlinear coagulation operator, denoted by C. This approach, initiated in [1], has been well developed for continuous coagulation-fragmentation models (though see [48,59,60] for the discrete version of the results), allowing for handling more singular fragmentation rates than the previously described method. However, since in a standard approach the nonlinear perturbation C is required to be Lipschitz continuous in the chosen state space, originally only bounded coagulation kernels were considered, see e.g.…”
Section: Some Historymentioning
confidence: 99%
See 3 more Smart Citations
“…Another approach, that is the subject of this paper, is based on semigroup theory, see e.g. [8], and consists in looking at (1) (or (6)) as a perturbation of the linear fragmentation semigroup by the nonlinear coagulation operator, denoted by C. This approach, initiated in [1], has been well developed for continuous coagulation-fragmentation models (though see [48,59,60] for the discrete version of the results), allowing for handling more singular fragmentation rates than the previously described method. However, since in a standard approach the nonlinear perturbation C is required to be Lipschitz continuous in the chosen state space, originally only bounded coagulation kernels were considered, see e.g.…”
Section: Some Historymentioning
confidence: 99%
“…Since, however, in general no simple description of the generator's domain was known, [8,Remark 8.16] or [4], the analyticity of the fragmentation semigroup was not studied. Fortunately, recently, [60], it has been proved that a simple fragmentation operator with uniform binary fragmentation generates an analytic semigroup in l 1 1 . This prompted interest in the topic and, subsequently, it was shown that a class of fragmentation operators, that includes physically relevant binary and homogeneous fragmentations, both in the discrete and continuous case, is sectorial albeit in a smaller space of densities that have finite higher moments (the space l 1 p := l 1 U with U = i p , p > 1, or its equivalent X 0,p = L 1 (R + , (1 + x p )dx) in the continuous case), [6,11].…”
Section: Some Historymentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, we obtain a pure fragmentation system that, however, is not mass conservative. Such systems were considered in Cai et al and Smith et al While mathematically they are equivalent to , physically they describe different models as in : The death process is independent of fragmentation, and in Cai et al, the mass loss is caused by the so‐called explosive fragmentation. Also, the study of death‐sedimentation process is of independent interest.…”
Section: Introductionmentioning
confidence: 99%